2004
DOI: 10.1051/forest:2004057
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of natural woody species regeneration for the conversion of Norway spruce plantations on alluvial soils

Abstract: -In the perspective of the conversion of Norway spruce plantations, there is a need for foresters to assess the potential of the natural woody species regeneration. We studied 50 Norway spruce plantations on alluvial soils throughout the Grand-duché de Luxembourg and compared the regeneration characteristics (species composition, spatial heterogeneity) with 42 riverine deciduous stands (the target communities). Within the Norway spruce plantations, Fraxinus excelsior and Acer pseudoplatanus were the main regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…It has recently been shown that the recruitment of a new spruce generation strongly depends on the quality of the seedbed [14,15,46]. This applies in particular for spruce, because spruce is a species with small seeds and therefore is more substrate-restricted than other tree species [27,35,37].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the recruitment of a new spruce generation strongly depends on the quality of the seedbed [14,15,46]. This applies in particular for spruce, because spruce is a species with small seeds and therefore is more substrate-restricted than other tree species [27,35,37].…”
Section: Introductionmentioning
confidence: 99%
“…Individual trees can produce up to 170,000 seeds that are easily carried by wind, mostly within 200 m distance of the parent tree (Rusanen & Myking, 2003;Hérault et al, 2004;Thies et al, 2009). Seedlings are very vulnerable to competitive herbs (Diaci, 2002;Modrý et al, 2004;Vandenberghe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds can be dispersed by wind or alternatively a combination of animals and gravity (Farmer 1997). Observations on the distribution of tree seedlings has shown that seed of some species can disperse 100 m or more, but most seed falls much closer to the parent tree (Johnson 1988;Karlsson 1996;Farmer 1997;Herault et al 2004). Investigations into seed dispersal into a Norway spruce clearcut found that only a small proportion of seed from wind-dispersed species penetrated more than 20 m into the clearcut and that birch spread the furthest of the seven species studied (Karlsson 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Whilst there were some differences between the forest types observed in this study and the relationships between vegetation, the occurrence of regeneration, the number of seedlings always was positively related to the proximity of parent trees. Consequently, whether conversion takes place gradually or by clearfelling, a species is unlikely to regenerate if it is distant from a parent tree and the probability of restocking is reduced at areas of a site remote from any parent trees (Herault et al 2004;Jonášová et al 2006). The potential for natural regeneration will vary and at most sites with few parent trees those species with light, wind-dispersed seeds such as birch and willow (Salix spp.)…”
Section: Discussionmentioning
confidence: 98%